Teologi Kontekstual dalam Ekspresi Sakral Tari Rejang Keraman di Bali - Wahyuni, I Gusti Ayu Desy (Jayapangus Press, 2025)
Rejang Keraman dance is part of the wali (sacred) dance tradition within Hindu rituals in Bali, commonly performed during religious ceremonies. Unlike other forms of wali dance, Rejang Keraman may be performed by both men and women and symbolically represents the manifestation of sacred feminine energy. However, scholarly studies on Rejang Keraman have primarily focused on its aesthetic and cultural dimensions, while theological approaches remain rare. This research addresses that gap by offering a novel theological analysis of the dance. The study aims to explore Rejang Keraman as a theological expression within the local context of Balinese Hinduism. The research was conducted in Kedis Village, Busungbiu District, Buleleng Regency, where the dance is a vital component of the Pujawali (temple anniversary) ceremony at the village temple. A qualitative method was employed, utilizing participatory observation, in-depth interviews, and literature review. Applying a contextual theological approach, the study interprets how Hindu religious values are practiced and understood dynamically within the framework of local culture. The findings reveal that Rejang Keraman functions not merely as an artistic performance but as a theological medium that bridges the relationship between humans, nature, and the divine. The practice reflects a spirituality that is inclusive and adaptive, offering a pathway for developing a contextual Hindu theology rooted in local traditions. The study recommends the preservation and reinterpretation of sacred local rituals as an essential foundation for formulating Hindu theological perspectives relevant to contemporary social dynamics.